2022
DOI: 10.1016/j.ymthe.2021.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficacy and safety of eladocagene exuparvovec in patients with AADC deficiency

Abstract: Aromatic L-amino acid decarboxylase deficiency results in decreased neurotransmitter levels and severe motor dysfunction. Twenty-six patients without head control received bilateral intraputaminal infusions of a recombinant adenoassociated virus type 2 vector containing the human aromatic L-amino acid decarboxylase gene (eladocagene exuparvovec) and have completed 1-year evaluations. Rapid improvements in motor and cognitive function occurred within 12 months after gene therapy and were sustained during follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
109
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(113 citation statements)
references
References 37 publications
3
109
0
1
Order By: Relevance
“…The first AAV trial was for treating cystic fibrosis using ​​tgAAV2-CFTR ( 1 ), and the first trial using AAV delivery for in vivo gene editing was for treating Mucopolysaccharidosis type I by zinc finger nucleases (NCT02702115) ( 29 ). There are four approved AAV gene therapy drugs: Glybera ( 30 ), Zolgensma ( 31 ), Luxturna ( 32 ), and Upstaza ( 33 ) and one conditional approval Roctavian ( 34 ) in the USA and/or EU.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first AAV trial was for treating cystic fibrosis using ​​tgAAV2-CFTR ( 1 ), and the first trial using AAV delivery for in vivo gene editing was for treating Mucopolysaccharidosis type I by zinc finger nucleases (NCT02702115) ( 29 ). There are four approved AAV gene therapy drugs: Glybera ( 30 ), Zolgensma ( 31 ), Luxturna ( 32 ), and Upstaza ( 33 ) and one conditional approval Roctavian ( 34 ) in the USA and/or EU.…”
Section: Resultsmentioning
confidence: 99%
“…Unknown status suggests that study has passed its completion date and status has not been verified in more than two years. Luxturna (32), and Upstaza (33) and one conditional approval Roctavian (34) in the USA and/or EU. A total of 182 trials disclosed dosing information, and the doses vary largely depending on ROA.…”
Section: Description Of 255 Clinical Trialsmentioning
confidence: 99%
“…Ghasemi et al 135 found that D-serine located in peripheral nerves could modulate neurogenic relaxation. What's more, L-tryptophan decarboxylase, 136 fatty acid synthase, 137 and nitric oxide synthase 138 were considered crucial in the central nervous system, such as myelination and re-myelination. The activity of various metabolic pathways could also be improved by GFNs, including central carbon metabolism in cancer, protein digestion and absorption, glycine, and tyrosine metabolism.…”
Section: Increase In Enzyme Activitymentioning
confidence: 99%
“…In the last three years, there has been a marked increase in the number of identified variants, as shown by the locus-specific database PNDdb ( accessed on 30 August 2022) that currently (August 2022) reports 420 variants, highlighting that the number of variants has exponentially increased ( Figure 1 ), with the compound heterozygous genotype contributing over 70% of genotypes [ 4 ]. The clinical trials of gene therapy based on adeno-associated virus delivered either to the putamen [ 5 , 6 , 7 , 8 , 9 , 10 ] or to the midbrain [ 11 , 12 ] could have boosted the interest in this rare disease. Gene therapy represents a hope for many patients and is an undoubtful great step for the approach to this disease that has been neglected and misdiagnosed for a long time [ 13 ].…”
Section: Introductionmentioning
confidence: 99%